2017
DOI: 10.1038/ng.3821
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants associated with mosaic Y chromosome loss highlight cell cycle genes and overlap with cancer susceptibility

Abstract: The Y-chromosome is frequently lost in hematopoietic cells, representing the most common somatic mutation in men. However, the mechanisms regulating mosaic loss of chromosome-Y (mLOY), and its clinical relevance, are unknown. Using genotype array intensity data and sequence reads in 85,542 men, we identify 19 genomic regions (P<5x10-8) associated with mLOY. Cumulatively, these loci also predicted X-chromosome loss in women (N=96,123, P=4x10-6). Additional epigenome-wide methylation analyses in whole blood high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
218
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(235 citation statements)
references
References 68 publications
15
218
2
Order By: Relevance
“…LOY is the most common known acquired human mutation in surveyed populations 96 , and its frequency increases with age ( Figure 3A), and is associated with smoking 97 . It has also been associated with decreased survival time from all causes ( Figure 3B), including cancer ( Figure 3C) 96 , and with increased risk of Alzheimer disease ( Figure 3D) 98 ; these associations have been replicated in some but not all studies [99][100][101][102] . The SNP rs2887399 near TCL1A on chromosome 14 is associated with LOY risk (OR = 1.55, 95% CI = 1.36-1.78; P = 1.37 x 10 -10 ) 101 and more recently 18 additional associated genomic regions have been identified 102,103 .…”
Section: Y-chromosomal Aneuploidymentioning
confidence: 89%
“…LOY is the most common known acquired human mutation in surveyed populations 96 , and its frequency increases with age ( Figure 3A), and is associated with smoking 97 . It has also been associated with decreased survival time from all causes ( Figure 3B), including cancer ( Figure 3C) 96 , and with increased risk of Alzheimer disease ( Figure 3D) 98 ; these associations have been replicated in some but not all studies [99][100][101][102] . The SNP rs2887399 near TCL1A on chromosome 14 is associated with LOY risk (OR = 1.55, 95% CI = 1.36-1.78; P = 1.37 x 10 -10 ) 101 and more recently 18 additional associated genomic regions have been identified 102,103 .…”
Section: Y-chromosomal Aneuploidymentioning
confidence: 89%
“…1,2 The results of this study, in conjunction with the previous reports by Shin et al 8 Furthermore, there are no data whether mLOY in young men is associated with early death and the risk of various disorders, as is the case for elderly people. 1,4,5 In this context, Thompson et al 3 raised questions about the pathogenicity of mLOY in blood cells.…”
Section: Discussionmentioning
confidence: 99%
“…1-3 Aging-related mLOY has been associated with shorter life expectancy and increased risks of cancer and other disorders. 1,4,5 The frequency of mLOY in men under 40 years of age remains unknown, but is predicted to be extremely low. 4,5…”
mentioning
confidence: 99%
“…Indeed, researchers have found that loss of the Y chromosome in men correlates with increased risk of Alzheimer’s disease and cancer (Dumanski et al, 2016; Forsberg et al, 2014). It is worth noting that general chromosomal instability predisposing to cancer may result in Y loss simply because this chromosome is easier to lose, so more research must be done to prove causality (Wright et al, 2017). Mosaicism is also a common phenomenon in women with TS; in fact, it is thought that all women with TS must be mosaic for cells of another karyotype, such as 46,XX, because ~99% of fetuses with a complete 45,X karyotype do not survive fetal development (Hook & Warburton, 1983, 2014).…”
Section: Experimental Models For Identifying Phenotypes Mediated By Smentioning
confidence: 99%